Case Report: PD-1 Blockade Combined Autologous Hematopoietic Stem Cell Transplantation With Modified BEAM Regimen Containing High-Dose Cytarabine to Treat R/R Hodgkin's Lymphoma - Wang, Xiaoqi; Cassady, Kaniel; Zou, Zhongmin; Zhang, Xi; Feng, Yimei (Frontiers in Medicine, 2021)
The emergence of new drugs has provided additional options in the treatment of relapsed and refractory (R/R) Hodgkin's lymphoma (HL). However, the use of autologous stem cell transplantation (ASCT) has not been completely replaced in this setting. The use of anti-programmed death-1 (PD-1) antibody bridging to ASCT and as maintenance after transplantation is a novel approach in HL treatment. In this case, we report that PD-1 monoclonal antibody (mAb) plus ASCT with modified BEAM regimen (carmustine + etoposide + cytarabine + melphalan) containing high-dose cytarabine to treat R/R HL may represent a promising regimen in this difficult-to-treat setting.